1999
DOI: 10.1111/j.1151-2916.1999.tb02132.x
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Shrinkage in Tape‐Cast Alumina: Role of Processing Parameters and Particle Shape

Abstract: Aqueous suspensions of alumina and other powders containing no visible morphological anisotropy were tape cast under different conditions to study the role of processing parameters and powder characteristics in the origin of inplane sintering shrinkage anisotropy. High anisotropic shrinkage, with the typical shrinkage in the transverse direction exceeding that in the casting direction by more than 10%, was observed for tape-cast alumina cast at high solids loading and high shear rates. Tape casting without any… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 16 publications
1
44
0
Order By: Relevance
“…However, even in the case of monolayer tape casting, it is of great importance to control the aforementioned shape instabilities. Raj and Cannon 14 proposed a formula to measure the percentage of anisotropic shrinkage in the tape casting process. They showed that the tape thickness and its variation have a great impact on the anisotropic shrinkage and the resultant mechanical properties, where an increase in the tape thickness causes a decrease in the anisotropic shrinkage.…”
Section: Introductionmentioning
confidence: 99%
“…However, even in the case of monolayer tape casting, it is of great importance to control the aforementioned shape instabilities. Raj and Cannon 14 proposed a formula to measure the percentage of anisotropic shrinkage in the tape casting process. They showed that the tape thickness and its variation have a great impact on the anisotropic shrinkage and the resultant mechanical properties, where an increase in the tape thickness causes a decrease in the anisotropic shrinkage.…”
Section: Introductionmentioning
confidence: 99%
“…This particle orientation is commonly observed in green bodies produced under conditions of strong shear stress, such as occur during tape casting, extrusion, or injection molding. [16][17][18] Particle orientation is also found in green bodies made by the compaction process or by slip casting, where the driving force for particle alignment would appear to be minimal. [19][20][21][22][23][24][25][26] Quantitative evaluation of particle orientation is the starting point for studying anisotropic sintering.…”
Section: -13mentioning
confidence: 99%
“…The methodology discussed is applicable for the systems with hydrostatic sintering stress, which is the case commonly used. Currently, discussions of anisotropic sintering and, hence, of a possibility of a non-hydrostatic sintering stress start to appear in literature (e.g., Tikare et al, accepted;Raj and Cannon, 1999;Stedman et al, 1993;Watanabe et al, 1989). Our methodology of calculating the sintering stress is not directly applicable to such a case.…”
Section: Discussionmentioning
confidence: 95%